KELAINAN FUNGSI HATI DAN GINJAL TIKUS PUTIH (Rattus norvegicus, L.) AKIBAT SUPLEMENTASI TAWAS DALAM PAKAN - Ratih Haribi; Sri Darmawati; Tri Hartiti (JURNAL KESEHATAN, 2009)
Abstract Alum is used to improve the quality of food containing toxic heavy metal ions which can interfere with Aluminum enzymatic system, and tissue damage. Liver and kidney are the most used network is affected, because it is a detoxification organ. Liver and kidney damage can be detected by an enzyme concentration of SGOT, SGPT, Billirubin, Protein, Ureum and Creatinin in the blood This study aims to find out the effects of alum in a feed supplement for liver and kidney damage in a clinic conducted from May to Oclober 2007, at the Laboratory of the University Clinic Patologt Muhammadiyah Semarang. Sample studies of white rats (Rattus norvegicus, L.), aged 2 months with weight average of 200 grams. 0o/o dose treatment (without supplementation), 0.05%, 0.1%, 0.2%, 0.5%, 1% and 0% (without supplementation), and subsequent treatment with a dose of 2%, 3%, 4%, 5 % and 6% volum, who every day put into the stomach of rats l0 mL Clinical laboratory tests performed at the time before treatment (control), 4 weeks, 6 weeks and 8 weeks of exposure time. Examination AST and ALT with Ultra Violet Test methods, Total Billirubin with modifications Groff Jendrasik method, total protein Colorimetri method, U Berthelot method, Creatinin Jaffe method. Clinical chemistry tests showed that supplementation influence of alum on the concentration of Enzymes and other factors in the blood of mice associated with damage to liver and kidney tissue. Level of organ damage significant with alum in a feed supplement. The higher the concentration of alum disuplementasion and the longer exposure time resulted in damage to the liver and kidneys getting worse.